RC-IAL cell line: sensitivity of rubella virus grow Linhagem celular RC-IAL: sensibilidade de crescimento do vírus da rubéola - Cristina A Figueiredo; Maria I Oliveira; Suely P Curti; Aurea S Cruz; Eliane Moreira; Ana MS Afonso; Luís Florêncio de Salles-Gomes (Universidade de São Paulo, 2000)
OBJECTIVE: The rapid growth of the rubella virus in RC-IAL² with development of cytopathic effect, in response to rubella virus infection, is described. For purposes of comparison, the rubella virus RA-27/3 strain was titered simultaneously in the RC-IAL, Vero, SIRC and RK13 cell lines. METHODS: Rubella virus RA-27/3 strain are inoculated in the RC-IAL cell line (rabbit Kidney, Institute Adolfo Lutz). Plates containing 1.5x10(5) cells/ml of RC-IAL line were inoculated with 0.1ml s RA-27/3 strain virus containing 1x 10(4)TCID50/0.1ml. A 25% cytopathic effect was observed after 48 hours and 100% after 96 hours. The results obtained were compared to those observed with the SIRC, Vero and RK13 cell lines. Rubella virus was detected by immunohistochemistry. RESULTS: With the results, it was possible to conclude that the RC-IAL cell line is a very good substrate for culturing rubella virus. The cells inoculated with rubella virus were examined by phase contrast microscopy and showed the characteristic rounded, bipolar and multipolar cells. The CPE in RC-IAL was observed in the first 48 hours and the curve of the increased infectivity was practically the same as observed in other cell lines. CONCLUSIONS: These findings are important since this is one the few cell lines described in the literature with a cytopathic effect. So it can be used for antigen preparation and serological testing for the diagnosis of specific rubella antibodies. OBJETIVO: Descreve-se o crescimento do vírus-padrão da rubéola RA-27/3 na linhagem celular RC-IAL, com desenvolvimento de efeito citopático em resposta à infecção viral. Para este propósito, o vírus-padrão foi titulado simultaneamente nas linhagens celulares Vero, SIRC e RK13. MÉTODOS: O vírus-padrão da rubéola RA-27/3 foi inoculado na linhagem celular RC-IAL (rim de coelho, Instituto Adolfo Lutz). Placas contendo 1,5x10(5) células/ml foram inoculadas com 0,1 ml do vírus contendo 1x10(4) DICT50/0,1 ml. O efeito citopático correspondente a 25% foi observado após 48 h e 100% após 96 h. Os resultados obtidos foram comparados com o crescimento do vírus nas linhagens celulares SIRC, Vero e RK13. O vírus da rubéola na linhagem celular RC-IAL foi detectado por imuno-histoquímica. RESULTADOS: As células inoculadas com o vírus da rubéola apresentaram efeito citopático nas primeiras 48h. As células apresentaram aspecto arredondado, com formação de alguns prolongamentos citoplasmáticos e sincícios, produzindo células multinucleadas. A curva do crescimento da infectividade do vírus foi praticamente a mesma que a observada nas outras linhagens celulares. CONCLUSÃO: Os resultados obtidos mostram que a linhagem celular RC-IAL é um ótimo substrato para crescimento do vírus da rubéola, pois poucas linhagens celulares descritas na literatura apresentam efeito citopático considerável e podem ser utilizadas para preparação de antígenos e nos testes de diagnóstico sorológico para o vírus da rubéola.